Construction contracts (or: how to get the right building at the right price?) - Surajeet Chakravarty; W. Bentley MacLeod (Institute for the Study of Labor (IZA), 2006)
Most contracts that individuals enter into are not written from scratch; rather, they depend upon forms and terms that have been successful in the past. In this paper, we study the structure of form construction contracts published by the American Institute of Architects (AIA). We show that these contracts are an efficient solution to the problem of procuring large, complex projects when unforeseen contingencies are inevitable. This is achieved by carefully structuring the ex post bargaining game between the Principal and the Agent. The optimal mechanism corresponding to the AIA construction form is consistent with decisions of the courts in several prominent but controversial cases, and hence it provides an economic foundation for a number of the common-law excuses from performance. Finally, the case of form contracts for construction is an example of how markets, as opposed to private negotiations, can be used to determine efficient contract terms.
Keywords: D8; K2; L7; 330; law and economics; incomplete contracts; construction; agency theory; industry studies; outsourcing; procurement